2018
DOI: 10.1051/matecconf/201818004001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wayside energy storage devices for DC heavy rail transport

Abstract: The proposed paper presents the possibility of using the wayside energy storage devices (WESD) for the DC Heavy Rail Transport treating the design, costs and payback time. Moreover a case study comparison for the use of wayside energy storage devices on the heavy transport at the supply voltage of 3.3kV DC is presented. A method of sizing the energy storage devices using vehicle characteristics, traction power supply and running timetable is presented. The paper also presents the cost analysis for the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Tables A1-A7 present typical input parameters used for simulation purposes in this paper. The information in the tables have been sourced from equipment manufacturers, technical papers or assumed according with engineering common practice [21][22][23][24][25][26][27][28][29][30][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tables A1-A7 present typical input parameters used for simulation purposes in this paper. The information in the tables have been sourced from equipment manufacturers, technical papers or assumed according with engineering common practice [21][22][23][24][25][26][27][28][29][30][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…As with the OESS the WESD can be equipped with a wide range of storage technologies (batteries, supercapacitors, flywheels, hydrogen) with the advantage that there are fewer space constraints to locate the WESD. There are different WESD manufacturers including Siemens (Sitras Static Energy Storage) implemented in Germany (Dresden, Cologne, Koln and Bochum), China (Beijing) and Spain (Madrid); Bombardier (EnerGstor) installed in Kingston (ON, Canada); ABB (Enviline) installed in Warsaw (Poland) and Hong Kong [25][26][27][28][29][30]. In [29] Ghaviha, Campillo, Bohlin and Dahlquist reviewed the use of WESD in light transport and concluded that some WESD can achieve 30% energy savings.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The first strategy (stationary ESS) is to arrange the ESS equipment at the traction substations (substation-inside ESS) or other elements of the traction power supply system (wayside ESS). Several literatures deal with the problems of implementations of the stationary ESS systems into DC traction power supply system of metro lines [2][3] and railway lines [6][7][8][9].…”
Section: Location Of Ess Equipment: Variants and Proposalsmentioning
confidence: 99%